Pendampingan Pengelohaan Pertanian Oragnik Dalam Rangka Peningkatan Ekonomi Masyarakat Kelurahan Tambunan Kecamatan Makale Utara Kabupaten Tana Toraja - Feny Veronicha Valensia; Friskayanti Tonapa; Carolina Paulus Polli; Maryuni Toding; Andi Irianto; Eka Kusumaningrat; Adelina Adelina; Selmi Lora Batara; Efriani Erika Jusiani; Friskayanti Friskayanti; Dina Ramba (Pusat Riset dan Inovasi Nasional, 2021)
Tambunan sub-district is a sub-district in North Makale sub-district, Tanah Toraja Regency which has abundant natural resource potential and utilization of existing natural resources. Tambunan sub-district is an area that has abundant natural resources. This article investigates how to integrate the use of natural resources into sustainable neighborhood development. The research methodology includes field work, stakeholder interviews, and analysis of secondary data regarding the economic and environmental conditions of the subdistrict. The results of the research show that the Tambunan sub-district has quite large potential to support development